2014
DOI: 10.1186/1472-6963-14-162
|View full text |Cite
|
Sign up to set email alerts
|

Time to antibiotics and outcomes in cancer patients with febrile neutropenia

Abstract: BackgroundFebrile neutropenia is an oncologic emergency. The timing of antibiotics administration in patients with febrile neutropenia may result in adverse outcomes. Our study aims to determine time-to- antibiotic administration in patients with febrile neutropenia, and its relationship with length of hospital stay, intensive care unit monitoring, and hospital mortality.MethodsThe study population was comprised of adult cancer patients with febrile neutropenia who were hospitalized, at a tertiary care hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 16 publications
1
48
0
1
Order By: Relevance
“…In addition, relatively small numbers of FN episodes were analyzed, making it more difficult to draw definite conclusions. More recently, Perron et al [17] reported the data of 105 patients with FN, showing a . Numbers and complication rates at hourly intervals from triage to antibiotics are shown using a histogram.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, relatively small numbers of FN episodes were analyzed, making it more difficult to draw definite conclusions. More recently, Perron et al [17] reported the data of 105 patients with FN, showing a . Numbers and complication rates at hourly intervals from triage to antibiotics are shown using a histogram.…”
Section: Discussionmentioning
confidence: 98%
“…Data on time to antibiotic administration are sparse, although two relevant studies 14,15 were found during preparation for this update. Perron et al 14 found a significant association on multivariate analysis between time to administration (TTA) and length of hospital stay, but not mortality or ICU monitoring.…”
Section: Clinical Questionmentioning
confidence: 99%
“…The time to commencement of antibiotics (AB) is critical in an oncologic emergency, where chemo‐related immunocompromised patients are at risk of being overwhelmed by neutropenic sepsis. Delays to commencement of AB have been shown to result in poorer clinical outcomes (Perron, Emara, & Ahmed, ).…”
Section: Introductionmentioning
confidence: 99%